(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Iron deficiency continues to be the leading cause of single nutrient deficiency in the world. In India 62-88% pregnant women suffer from anemia, out of which 80% is due to iron deficiency. Iron deficiency anaemia is completely preventable with iron supplementation. This study was conducted to know whether low dose weekly oral iron regimen is an effective alternative to daily regimen in preventing iron deficiency in pregnancy.